BIAS GENDER DALAM PEMILIHAN PRAJURU DESA ADAT TENGANAN PEGRINGSINGAN, MANGGIS, KARANGASEM - Widawan, I Kadek Krisna; Erviantono, Tedi; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2017, 2017)
The apad ulu system is a marriage sequence system for structural filling of the Prajuru of Customary Village. Patriarchy is still very inherent in the customary order, like ulu apad. Women seem to just follow the order made the majority by men. The research entitled "Gender Bias in the Selection of Prajuru of Customary Village Tenganan Pegringsingan, Manggis, Karangasem” aimed to provide exposure and description of gender bias in the selection of Prajuru in Customary Village Tenganan Pegringsingan, Manggis, Karangasem. This research used descriptive qualitative research method with in-depth interview. The theoretical basis used was the queer theory which mentioned identity was always associated with the labeling and regulated by universal law. Based on the analysis of the data obtained the findings that, first there was no election in the determination of positions because women automatically follow the position of their spouses. Second, dominant decision making in men; third, meeting is more routinely attended by men; fourth, women could not replace their partner position.   Key words : Gender Bias, Representation, Customary Villages